Pengembangan Lab Sheet Praktikum Geomatika II untuk Program Studi S1 PTSP FT UNY - felia marva (Jurnal Pendidikan Teknik Sipil, 2022)
The aims of this study were to: (1) develop a lab sheet as a material to support the learning process in the Geomatics II Practicum subject in the Civil Engineering and Planning Department, Yogyakarta State University and (2) determine the feasibility of the lab sheet in the Geomatics II Practicum subject in the Civil Engineering department. and Planning of Yogyakarta State University.The method used in this research is Research and Development Research and Development (R&D). The model used is 4D Thiagarajan, namely: (1) Define, (2) Design, (3) Develop, (4) and Disseminate. The lab sheet feasibility test is carried out by material and media expert validators. Lab sheet development trials were conducted on 42 students as respondents. Data collection in this study used a questionnaire with a Likert scale of 1-5 while the data analysis technique was quantitative descriptive analysis by looking for the average price.Based on the results of the research, the Geomatics II practicum lab sheet received a feasibility score of 95% from the material expert validator in the "Very Eligible" category, the feasibility value of the media expert validator was 79% in the "Eligible" category, and student respondents scored 91% in the " Very Worthy". This shows that the Geomatics II Practicum lab sheet is feasible to be used as teaching material in the Geomatics II Practicum course.